The Novel LncRNA WASH5P Inhibits Colorectal Cancer Carcinogenesis via Targeting AKT Signaling Pathway - Wei, Hongyun; Mao, Tao; Zhang, Qian; Ren, Keyu; Qi, Xingsi; Zhang, Yunmei; Cao, Bin; Jin, Yanchun; Tian, Zibin; Ren, Linlin (Frontiers in Oncology, 2022)
Emerging evidence has shown that long non-coding RNAs (lncRNAs) play an important role in colorectal cancer (CRC) carcinogenesis, so more specific mechanisms of key lncRNAs in CRC initiation and development are needed. Here we evaluated the expression profiles of lncRNAs in CRC tissues and identified a novel lncRNA generated from the pseudogene WASP family homolog 5, termed lncRNA WASH5P. However, the role and potential molecular mechanisms of this novel LncRNA in CRC carcinogenesis is unknown. Our present study found that WASH5P was significantly downregulated in CRC cell lines and tissues compared with normal controls. Ectopic expression of WASH5P in CRC cells could significantly inhibit CRC cell proliferation, invasion and migration through increasing epithelial marker and decreasing mesenchymal marker expressions. WASH5P overexpressing CRC cells developed tumors more slowly in different mouse models. Furthermore, rescue experience demonstrated WASH5P could lead to CRC tumorigenesis via AKT phosphorylation and AKT pathway activation. Thus, our findings suggested that a novel lncRNA WASH5P might be a candidate biomarker and therapeutic target which could inhibit the proliferation, migration, invasion, and EMT of CRC though activating AKT pathway.